Pengaruh Manajemen Kelas Terhadap Kualitas Pembelajaran Mata Pelajaran IPS Terpadu - Israh Israh; Rosman Ilato; Melizubaida Mahmud; Usman Moonti; Roy Hasiru; Sudirman Sudirman; Imam Prawiranegara Gani (Journal of Economic and Business Education, 2023)
The research aims to determine the effect of classroom management on the learning quality of Integrated Social Science subject in grade VIII at SMP Negeri 1 Tilamuta, Boalemo Regency. This study employs a quantitative method. The data collection is carried out through observation, questionnaires, and documentation. The population includes 121 students and 36 students, as samples are taken from the population. The analysismethod uses simple linear regression. The research finding shows that class managemment affects the learning quality in the Integrated Social Science Subject grade VIII at SMP Negeri 1 Tilamuta, Boalemo Regency, with a significant effect of 45,3%